Growth responses of Quercus fusiformis (Fagaceae) to ectomycorrhizal inoculation with Boletus luridellus - Quiñonez Martínez, Miroslava (2022)
https://myk.univie.ac.at/wp-content/uploads/2022/04/OZP29_Fortunato_Boletus_luridellus.pdf